2019
DOI: 10.1177/0030222819837778
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom as the Mediator in the Relationships Between Meaning in Life and Attitude Toward Death

Abstract: The goal of the presented research was to investigate if wisdom plays a mediating role in the relationships between meaning in life and the attitude toward death in the period of middle and late adulthood. A study was carried out that included 567 persons aged 40 to 75 years. Three measures were used: Personal Meaning Profile, Three-Dimensional Wisdom Scale, and Death Attitude Profile-Revised. The conducted analyses allowed the authors to confirm the mediating role of wisdom in the relationships between meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
(121 reference statements)
0
9
0
1
Order By: Relevance
“…Despite this difference, some key concepts for psychosocial and existential theory seem to be interrelated and "are part of a common nomological web associated with the nature of wellbeing" (Waterman, 2014, p. 43). In fact, it seems that Erikson's model allows for a better understanding and explanation of a number of existential issues, shedding light on such questions as (a) the continuity of the sense of self in time and the consistency of functioning in the important areas of life based on personal decisions, values, and goals; (b) the importance of commitment for well-being; and (c) the determinants of attitude toward death (Waterman, 2014;Brudek & Sekowski, 2019;Se Rkowski, 2019).…”
Section: The Erikson Model: a Meeting Between Essentialism And Existentialismmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this difference, some key concepts for psychosocial and existential theory seem to be interrelated and "are part of a common nomological web associated with the nature of wellbeing" (Waterman, 2014, p. 43). In fact, it seems that Erikson's model allows for a better understanding and explanation of a number of existential issues, shedding light on such questions as (a) the continuity of the sense of self in time and the consistency of functioning in the important areas of life based on personal decisions, values, and goals; (b) the importance of commitment for well-being; and (c) the determinants of attitude toward death (Waterman, 2014;Brudek & Sekowski, 2019;Se Rkowski, 2019).…”
Section: The Erikson Model: a Meeting Between Essentialism And Existentialismmentioning
confidence: 99%
“…Essentially, in late adulthood, the perspective of death can cause two types of effects: on the one hand, it stimulates the growth of ego synthesis and life wisdom; and on the other, it arouses terror and a sense of disintegration. Ambivalence in the field of attitude toward death is one of the key dimensions of the developmental crisis of the old age: ego integrity versus despair (Brudek & Sekowski, 2019;Se Rkowski, 2019). As Erikson points out, the awareness, acceptance, and integration of the inevitability of one's death is a key component of maturity in life (Erikson, 1950(Erikson, , 1959(Erikson, , 1968Erikson & Erikson, 1997).…”
Section: Old Agementioning
confidence: 99%
See 2 more Smart Citations
“…The difference between genders is mainly reflected in the affective dimension of wisdom (as shown in Table 2 and Figure 2 ). Using 3D-WS, researchers found that women scored significantly higher than men on the affective dimension ( Cheraghi et al, 2015 ; Brudek and Sekowski, 2019 ). This dimension refers to showing compassion, benevolence, positive emotions and behavior toward people, and the motivation to promote their wellbeing.…”
Section: Gender and Wisdom Levelmentioning
confidence: 99%